2014
DOI: 10.1111/jai.12588
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in gonadal sex differentiation and the dimorphic expression pattern in undifferentiated gonads of Russian sturgeonAcipenser gueldenstaedtiiBrandt & Ratzeburg, 1833

Abstract: The establishment of a sexing technique at an early developmental stage is an important issue in sturgeon aquaculture, yet the mechanism of sex differentiation in sturgeons remains poorly understood. This study aimed to identify genes involved in gonadal sex differentiation and to investigate sexually dimorphic gene expression in undifferentiated gonads. RNA-seq analyses using next-generation sequencers were carried out on undifferentiated gonads of five 9-month-old juvenile Russian sturgeon Acipenser gueldens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…It is interesting that ar expression increased during this period, suggesting that androgens are relevant for both male and female gonadal development. In contrast with our previous results in Siberian sturgeon (Berbejillo et al, ), but consistent with previous studies in other sturgeons (Amberg et al, ; Hagihara et al, ), dmrt1 was not sex ‐ dimorphic during this period. We speculate that the differences between the present and previous studies (Berbejillo et al, ) may be related to the age of the fish analyzed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is interesting that ar expression increased during this period, suggesting that androgens are relevant for both male and female gonadal development. In contrast with our previous results in Siberian sturgeon (Berbejillo et al, ), but consistent with previous studies in other sturgeons (Amberg et al, ; Hagihara et al, ), dmrt1 was not sex ‐ dimorphic during this period. We speculate that the differences between the present and previous studies (Berbejillo et al, ) may be related to the age of the fish analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…When using the presence of invaginations as the criterion for sex differentiation, the age when differentiation occurs was reported to vary from 4 to 9 months among sturgeons species (Chen et al, 2006;Flynn and Benfey, 2007;Grandi et al, 2007;Grandi and Chicca, 2008;Rzepkowska and Ostaszewska, 2013). This superficial distinction does not, however, provide conclusive evidence of morphological sex differentiation (Hagihara et al, 2014). We instead considered the presence of mitotic or meiotic germ cell clusters as a clear sign of ovarian development, whereas the homogeneous distribution of non-meiotic germ cells indicated presumptive males.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are consistent with previous studies in Russian sturgeon with no observation of sexual dimorphic expression pattern of sox9 in undifferentiated gonads (Hagihara et al . ). Similarly, our finding is consistent with previous studies on Siberian sturgeon, which states that sox9 play role in late testis differentiation (Berbejillo et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, several studies investigated the expression of sox9 during gonadal sex differentiation in different fish species (Jorgensen, Morthorst, Andersen, Rasmussen & Bjerregaard ; von Schalburg, Yasuike, Yazawa, De Boer, Reid, So, Robb, Rondeau, Phillips & Davidson ; Smith, Guzmán & Luckenbach ), only few studies have been reported in sturgeons (Berbejillo et al . ; Hagihara, Yamashita, Yamamoto, Ishihara, Abe, Ijiri & Adachi ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, all efforts to identify sex determination genes or even a sex‐linked marker in sturgeons have been unsuccessful (Wuertz et al , ; Keyvanshokooh et al , ; McCormick et al , ; Yarmohammadi et al , ). Few studies reported the expression of genes involved in ovarian differentiation such as foxl2 and cyp19a1a in sturgeon species (Hagihara et al , ). The role of ooestrogens, foxl2 and cyp19a1a in ovarian differentiation, however, was not reported in this group of fishes.…”
Section: Name Sequence and Annealing Temperature (T) Of Primers Usedmentioning
confidence: 99%